Design of English Teaching Corpus Resource-Sharing System Based on XML Technology - Bing, Li (Mathematical problems in engineering, 2022)
It is well known that vocabulary is the cornerstone of language learning. Therefore, vocabulary teaching is very important in English language teaching. However, time-consuming and inefficient vocabulary education has always been a long-standing issue. Teachers utilize traditional teaching methods, which are monotonous, so students lose interest and desire in studying, resulting in a drop in academic performance and even resistance to English courses, creating a vicious circle. Therefore, improving the efficiency of vocabulary teaching has become a hot topic in the field of English education today. Corpus technology has begun to infiltrate the realm of English education as the times and technology have progressed. Because of its vast capacity and real corpus, the corpus is gradually being used in English classes. Therefore, this research will explore the application of corpus-based XML technology data-driven teaching in junior high school English vocabulary teaching. Data-driven vocabulary teaching based on corpus resources has been shown to considerably improve students’ vocabulary learning effects, but its promotion requires the assistance of education departments as well as the development of instructors’ professional theoretical understanding. In order to solve the problem of data processing and data sharing of heterogeneous data in the process of digital campus construction, this study aims at the campus network application system, using data exchange technology and XML’s good extensibility, self-description, separation of form and content, etc. It realizes data sharing and sharing in heterogeneous databases.